Sequential Conditioning Un-manipulated Haploidentical Hematopoietic Stem Cell Transplantation in A Patient with High Risk and Refractory Acute Myeloid Leukemia by Using A Second-degree Relative Donor - Poolcharoen, Akkapon (Greater Mekong Subregion Medical Journal, 2022)
Following the second course of induction chemotherapy, only 10 to 20 percent of patients with relapsed/refractory acute myeloid leukemia can achieve complete remission. We reported the case of a patient with high-risk, refractory acute myeloid leukemia who underwent sequential conditioning T cell-replete haploidentical hematopoietic stem cell transplantation with post-transplant cyclophosphamide from a second-degree relative donor. The sequential conditioning regimen consisted of thiotepa 5 mg/kg on days -15 and -14, etoposide 100 mg/m2 on day-13 to -10, cyclophosphamide 400 mg/m2 on day-13 to -10, and mesna on day-13 to -10, followed by fludarabine 30 mg/m2 on day-6 to -2, and melphalan 140 mg/m2 on day-2. The graft-versus-host disease prophylaxis regimen consisted of cyclophosphamide, tacrolimus, and mycophenolate mofetil. Neutrophil and platelet engraftment occurred on day +15 and +32. On day+56, the patient developed CMV reactivation, which was successfully treated with ganciclovir. The last follow-up was on day +300; the patient remained in complete remission. He had mild chronic graft-versus-host disease of the oral mucosa, mild anemia, and mild thrombocytopenia. This patient demonstrated that sequential conditioning T cell- replete haploidentical hematopoietic stem cell transplantation utilizing a second-degree relative donor is feasible and may be a promising therapy option for patients with relapsed/refractory acute myeloid leukemia.